Climate Literacy and Innovations in Climate Change Education Distance Learning for Sustainable Development (Climate Change Management,, 2018)
This book addresses the links between climate change and the threats it poses to sustainable development, from a distance education perspective. Discussing current trends and challenges in sustainable development education, climate literacy and innovations in climate change education, it contributes to the global debate on the implementation of education for sustainability. It also assesses the role that e-learning can play in this process, addressing pedagogical concepts as well as the wide range of technological options now available.